Programming and Constructing Model of Four-Wheel Steering System - Dương Nguyễn Hắc Lân; Nguyễn Trung Kiên; Huỳnh Nguyễn Nhật Khương (Journal of Technical Education Science, 2025)
This article studies the method of programming and controlling rear axle steering depending on input signals consisting of the speed of the vehicle, and steering wheel angle to modelize the RWS system besides simplifying the design of suspension serving for RWS. This paper applies mathematic equations, arithmetic equivalence, and the theoretical basis of dynamic and kinematics of vehicle turning to create the algorithm and select suitable adaptors. The consequences of the research are based on mathematical formulas and simulation of Matlab/Matlab Simulink about the characteristic curve of the ratio of steering angles relying on linear speed. In conclusion, Although RWS is not a recent issue, its applicability and popularity level are low. Therefore, via this research article, the authors intend to contribute a design for the RWS system for the purpose of proving the ability of operation as well as the practical application of the model.